2018
DOI: 10.1096/fj.201700661rr
|View full text |Cite
|
Sign up to set email alerts
|

Perturbed bone composition and integrity with disorganized osteoblast function in zinc receptor/Gpr39‐deficient mice

Abstract: Changes in bone matrix composition are frequently found with bone diseases and may be associated with increased fracture risk. Bone is rich in the trace element zinc. Zinc was established to play a significant role in the growth, development, and maintenance of healthy bones; however, the mechanisms underlying zinc effects on the integrity of the skeleton are poorly understood. Here, we show that the zinc receptor (ZnR)/Gpr39 is required for normal bone matrix deposition by osteoblasts. Initial analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…A representative schematic of the molecular mechanism is shown in Figure 10. In agreement with our findings, a recent study showed that GPR39 knockout mice had weak bones as a result of abnormal bone composition, while cultured GPR39 null osteoblasts show low collagen matrix and abnormal matrix deposition [21]. Therefore, GPR39-mediated osteoblast differentiation appears to be vital both in vitro and in vivo, indicating its significant role in controlling bone formation.…”
Section: Discussionsupporting
confidence: 92%
“…A representative schematic of the molecular mechanism is shown in Figure 10. In agreement with our findings, a recent study showed that GPR39 knockout mice had weak bones as a result of abnormal bone composition, while cultured GPR39 null osteoblasts show low collagen matrix and abnormal matrix deposition [21]. Therefore, GPR39-mediated osteoblast differentiation appears to be vital both in vitro and in vivo, indicating its significant role in controlling bone formation.…”
Section: Discussionsupporting
confidence: 92%
“…The endogenous Zn 2+ , released during physiological activity, acts as a first messenger and triggers intracellular Ca 2+ signaling via the specific Gαq-coupled receptor ZnR/GPR39 [ 34 , 56 ]. Activity of ZnR/GPR39 in tissues relevant to Zn 2+ signaling has been identified in neurons, colon epithelial cells (colonocytes), skin epidermal cells (keratinocytes), pancreatic cells, prostate cancer cells, salivary gland cells, and in bones [ 57 , 58 , 59 , 60 , 61 ]. In neurons, stimulation of the mossy fibers triggers ZnR/GPR39-dependent Ca 2+ rises in postsynaptic CA3 (Cornu Ammonis 3) neurons [ 62 ] that are diminished in the presence of a non-permeable Zn 2+ chelator, or in the absence of the Zn 2+ transporter-3 (ZnT3), which is responsible for synaptic Zn 2+ accumulation.…”
Section: Identification Of a Zn 2+ -Sensing Recmentioning
confidence: 99%
“…While several zinc transporters of the ZIP family have been associated with skeletal function [ 137 ], a role for ZnR/GPR39 was not described. Using GPR39 knockout mice, a recent study indicates that this receptor is important for osteoblast differentiation [ 61 ]. Hence, mice lacking ZnR/GPR39 showed impaired bone composition with decreased collagen content, likely involving ADAMTS metalloproteinase, which regulates collagen processing [ 61 ].…”
Section: A Role For Znr/gpr39 In Diseasementioning
confidence: 99%
See 2 more Smart Citations